2002
DOI: 10.3168/jds.s0022-0302(02)74253-7
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Treating Whole-Plant Barley with Lactobacillus buchneri 40788 on Silage Fermentation, Aerobic Stability, and Nutritive Value for Dairy Cows

Abstract: Chopped barley forage was ensiled untreated or treated with several doses (1 x 10(5) to 1 x 10(6) cfu/g of fresh forage) of Lactobacillus buchneri 40788 in laboratory silos and untreated or treated (4 x 10(5) cfu/g) in a farm silo. Silage from the farm silos was fed to lactating cows. In the laboratory silo, the effects of inoculation on fermentation and aerobic stability were also compared to silage treated with a commercial inoculant and a buffered propionic acid additive. Inoculation with L. buchneri 40788 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
45
3
23

Year Published

2004
2004
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(83 citation statements)
references
References 20 publications
12
45
3
23
Order By: Relevance
“…Apesar de não ter sido detectada redução significativa na concentração de etanol, a redução das perdas indica que houve controle no desenvolvimento de leveduras na silagem inoculada com L. buchneri. A aplicação de L. buchneri tem resultado em silagens com 3,6 a 5,0% de ácido acético na MS Taylor et al, 2002). Concentração de 2% de ácido acético na MS, equivalente a 6,7 g do ácido por litro da fase líquida de uma forragem com 25% de MS, é suficiente para o controle de leveduras, visto que leveduras são normalmente controladas por concentrações de ácido acético superiores a 5,6 g/L do meio de cultura (94 mmol/L) (Woolford, 1975).…”
Section: Resultsunclassified
“…Apesar de não ter sido detectada redução significativa na concentração de etanol, a redução das perdas indica que houve controle no desenvolvimento de leveduras na silagem inoculada com L. buchneri. A aplicação de L. buchneri tem resultado em silagens com 3,6 a 5,0% de ácido acético na MS Taylor et al, 2002). Concentração de 2% de ácido acético na MS, equivalente a 6,7 g do ácido por litro da fase líquida de uma forragem com 25% de MS, é suficiente para o controle de leveduras, visto que leveduras são normalmente controladas por concentrações de ácido acético superiores a 5,6 g/L do meio de cultura (94 mmol/L) (Woolford, 1975).…”
Section: Resultsunclassified
“…The heterofermentative bacteria Lactobacillus buchneri converts lactic acid to acetic acid, 1,2 propanediol, propionic acid, CO 2 and traces of ethanol (Oude Elferink et al, 2001); acetic acid has a relatively high fungicidal effect. Inoculation with L. buchneri reduced yeast counts and improved aerobic stability in corn and high moisture corn silages (Ranjit & Kung Junior, 2000;Taylor et al, 2002). In sugarcane silages, inoculation with this bacteria reduced ethanol concentration and decreased DM loss (Pedroso, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Bulls fed TMR containing sugarcane silage inoculated with L. buchneri had higher DMI (P = 0.006; Table 4). Several studies have shown that when cattle or sheep are fed silages treated with L. buchneri, DMI is not affected (Driehuis et al, 1999;Taylor et al, 2002;Ranjit et al, 2002;Kung et al, 2003). However, in the present study, the inoculants were effective in mitigating NDF accumulation caused by sugar oxidation during the ensiling process and improved the DMI.…”
Section: Resultsmentioning
confidence: 45%